Heterosexual Parents’ Experiences of Their Donor-Conceived Children’s Search for and/or Contact with Their Donors in New Zealand Prior to Identity-Release Provisions - Duff, MA; Goedeke, S (Informa UK Limited, 2025)
Research suggests that donor conceived persons (DCP) may not only be interested in their genetic information, but in meeting donors and other genetically related individuals. While parental disclosure to donor conceived children (DCC) appears to be increasing, limited research examines the impact of disclosure and donor linking for DCP and parents. This research explores the experiences of nine heterosexual parents in New Zealand who mostly conceived prior to identity-release provisions and whose DCC have searched for or had donor contact. Data was collected via semi-structured interviews and analysed using thematic analysis. Findings suggest that parents valued their children’s access to genetic origins and viewed donor linking as a natural outcome of disclosure. Parents positioned themselves as facilitators or supporters of linking, while emphasising that linking should be DCP led. Donor and donor family willingness were noted as key in enabling contact. Early disclosure and support for linking were held to strengthen parent-child relationships, while later disclosure and difficulty in linking were associated with relationship tension. Relationships with donors ranged from distant to familial, with most parents noting that DCC valued connections with siblings. Parents reflected on the significant impacts of family-building through donor conception and the need for ongoing support.
Keywords: Donor conception; donor linking; egg donation; gamete donation; parental disclosure; sperm donation; 3215 Reproductive Medicine; 32 Biomedical and Clinical Sciences; Clinical Research; Behavioral and Social Science; Pediatric; 1103 Clinical Sciences; 1114 Paediatrics and Reproductive Medicine; Obstetrics & Reproductive Medicine; 3215 Reproductive medicine; Humans; New Zealand; Female; Male; Adult; Parents; Parent-Child Relations; Heterosexuality; Tissue Donors; Insemination, Artificial, Heterologous; Donor Conception; Child; Humans; Insemination, Artificial, Heterologous; Heterosexuality; Parent-Child Relations; Parents; Adult; Child; Tissue Donors; New Zealand; Female; Male; Donor Conception; Humans; New Zealand; Female; Male; Adult; Parents; Parent-Child Relations; Heterosexuality; Tissue Donors; Insemination, Artificial, Heterologous; Donor Conception; Child